DESKRIPSI KELAYAKAN BUKU TEKS TEMA 6 CITA-CITAKU SUBTEMA 1 AKU DAN CITA-CITAKU SISWA KELAS IV SEKOLAH DASAR NEGERI 18 SUNGAI KAKAP - Juliansyah, Rian; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to describe the feasibility of the 2013 SD/MI Curriculum Textbooks for fourth grade students with theme 6 My ideals Subtheme 1 I and my ideals according to Masnur Muslich's theory in terms of content assessment, presentation, linguistic and graphic aspects. This research is included in the descriptive type of qualitative research. Data collection techniques used in this study were interviews, observation and documentation. The qualitative data analysis technique used is the Miles and Hubermen interactive model. To test the credibility of the data on the results of the study using technical triangulation and source triangulation. The book under study is a 2013 SD/MI curriculum textbook for fourth grade students, theme 6 Sub-theme 1 I and my ideals, published by the Ministry of Education and Culture of the Republic of Indonesia in 2017. The results of this study indicate the assessment in the 2013 SD/Curriculum textbook. MI Student grade IV theme 6 My ideals Subtheme 1 Me and my ideals from the aspects of content feasibility, presentation feasibility, linguistic feasibility, and book graphic feasibility according to indicators to assess the feasibility of textbooks. the final score is 100. However, in terms of presentation feasibility, the examples of questions and learning activities are considered inappropriate because they do not contain examples of questions and in the glossary section there is no understanding and explanation of the terms used in the textbook with a final score 85. Then on the linguistic feasibility, the grammatical accuracy and spelling accuracy are assessed according to partly obtained a final score of 93. On the feasibility of the Graphics section the harmony of the layout was assessed in part with the final score of 97.Keywords : Description, textbook feasibility, thematic learning, BSNP